Ultrafast and Chemically Stable Transfer of Au Nanomembrane Using a Water-Soluble NaCl Sacrificial Layer for Flexible Solar Cells - Dong, Wan Jae; Kim, Sungjoo; Park, Jae Yong; Yu, Hak Ki; Lee, Jong Lam (ACS Applied Materials and Interfaces, 2019)
Large-scale industrial application of flexible device has called for development of transfer methods that deliver high yield and stability. Here, we show an ultrafast and chemically stable transfer method by using a water-soluble NaCl sacrificial layer. Extremely thin (10 nm) and large-area (4 in. wafer) free-standing Au nanomembranes (NMs) prepared on silicon substrate were successfully transferred to flexible PDMS substrate by dissolving the NaCl sacrificial layer. This transfer method enables highly transparent and electrically conductive Au NMs on PDMS substrate. To transfer a multilayered optoelectronic device, we fabricated flexible hydrogenated amorphous silicon (a-Si:H) solar cell on a glass substrate and transferred it to a PDMS substrate. There was no degradation of the electrical characteristic of the solar cell after the transfer. This approach enables the integration of high-temperature-processed a-Si:H solar cell onto low-temperature tolerant flexible polymer substrate without chemical contamination or damage.
Keywords: Electrical characteristic; Electrically conductive; Flexible polymer substrates; Flexible solar cells; Hydrogenated amorphous silicon (a-Si:H); Nanomembranes; Sacrificial layer; transfer; flexible solar cell; nanomembrane; sacrificial layer; sodium chloride; transfer